Pengembangan Hasil Akreditasi Madrasah Melalui Pemanfaatan Literasi Digital Guru Madrasah Aliyah Negeri 1 Aceh Tengah - Ikhsan, Ikhsan; Iskandar, Iskandar; Bahri, Saiful (Indonesian Journal of Islamic Educational Management, 2025)
The objectives of this study are to determine the competence of teachers in utilizing digital technology in developing madrasah accreditation. Then to find out how the implementation of digital teacher literacy culture. Methodology: This study is a phenomenological study with a descriptive qualitative approach. Collecting data obtained from observation, interviews and documentation. Data analysis techniques using the Miles and Huberman model. Main Findings: This study shows that the competence of teachers at Madrasah Aliyah Negeri 1 Aceh Tengah is very good, supported by the existence of programs that can provide opportunities for teachers to participate in utilizing information technology so that the digital literacy culture of teachers in madrasahs grows well, these activities include filling out student report cards based on applications, digital research classes and the use of the "explore knowledge" application, in addition to supporting the development of digital literacy, school teachers also provide online application-based learning called e-learning. This program is also implemented well following accurate procedures by implementing a good management system. Supporting factors in improving teachers' digital literacy competence include the availability of adequate facilities and infrastructure and internet networks. The novelty/originality of this study: the use of teacher digital literacy in developing madrasah aliyah accreditation